The digital code. About the statute of contemporary architecture - Trachana, Angelique (Arte, Individuo y Sociedad, 2013)
This paper aims to study the relationships and influences that exist between the conception of contemporary architecture and communication and information technologies pointing out its profound changes brought by that. The method to conduct this research traces the evolution of modern aesthetic theories verifying a process that leads to the aesthetics of virtual objects. In this process, is found, in critical key, the relationship between the most significant trends in architecture from the sixties with a theory of communication based on pure-visual parameters. The digital code is an absolute visual code and so the project processes completely produced by computer is submited to a review claiming bodily experience of architecture. One sees, however, a possibility to optimize new technologies in shaping human spaces and better living.